MUSEUM POS YOGYAKARTA PENEKANAN PADA TATA PENCAHAYAAN SEBAGAI PEMBENTUK RUANG - , FATTAH AKBAR ([Yogyakarta] : Universitas Gadjah Mada, 2014)
PT . Pos Indonesia has become a unifying cultural diversity throughout the country among the human family in a variety of cultural and community groups . Pos Indonesia role of provider of courier services and mail delivery of goods has considerably evolved into logistics business developer , property , financial services and even retail . Existence would be evidence and witness the history of the development of human civilization . Museum are needed to save and document the work of science and embodiment of human culture . museum is to build a future potential to unify past. Yogyakarta was chosen because it has a good factor in the field of culture and tourism education. Yogyakarta as City of Culture because have diverse cultures such as Mataram , Indische , Colonial , and Chinatown. Yogyakarta has a First at the University of Indonesia, Gadjah Mada University . Since then Yogyakarta has its own attraction for the youth from all over the country to study in the city . Not only known for its cultural wealth . Yogyakarta was granted by abundant natural resources like mountains in the north and beaches in the south to become a famous tourist destination in Indonesia and Abroad. Museum was designed with the concept of infill design and contrast . Museum adjoining the large post office requires continuity between functionality and architectural elements of the building that has an identity as a whole . The contrast of the museum gives a new identity to the region and the response of buildings on the environment by design today.